Mastering Finance and Accounting - Farrow David (Mcgraw Hill Book Company, 1994)
A unique, comprehensive text that covers the elements of accounting, cost and management accountancy and business financing. Preface, Accounting, The Fundamentals, Writing the Book, Reading the Book, Developing the Story, Accountancy - A Creative Exercise, Presenting Accounts, Interpreting Accounts and Judging Performance, Accounting for Cash, Keeping Your Eyes on the Bank, Sharing the Workload, Miscellaneous Matters, Manufacturing Accounts, Consolidation, Financing, Financing a Business, Financing Proposals, Costs and Budgets, Costs are Critical, Direct Costs, Overheads, Cost as an Aid to Decision Making, Accounting, Limited Companies, Cash Flow Statements, Interpretation of Company Accounts by Ratio Analysis, Clubs, Partnerships, Incomplete Records, Index.